A case of ectopic cilia - Güler, Mete; Yilmaz, Turgut; Güler, Özlem (Kluwer Academic Publishers, 2009)
Ectopic cilia are the most rare of cilial anomalies. We report a 27-year-old man who presents with tarsal conjunctival symptomatic ectopic cilia. On slit-lamp examination eversion of the lower eyelid demonstrated that several black - white cilia were protruding from the conjunctiva. © Springer Science+Business Media B.V. 2008.
Keywords: Conjunctiva; Ectopic cilia